EPIDEMIOLOGICAL PATTERN OF MANDIBULAR FRACTURES IN ISLAMABAD - Dr Musa Cheema; Dr Khadija Irshad; Dr Maniha Musarrat; Dr Sibtul Hassan; Dr Mahnoor Haroon; Dr Eman Haroon (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: In the realm of maxillofacial injuries, trauma stands out as the primary cause, with mandibular fracture being the second most prevalent type. Mandibular fractures represent a significant portion of cases involving facial trauma. The primary culprits behind facial fractures are high-impact incidents such as motor vehicle accidents, physical altercations, sports-related injuries, and work-related mishaps. Depending on the severity of the trauma endured, mandibular fractures can affect a single site or involve multiple anatomical sites simultaneously. Individuals who have sustained a fracture in the lower jaw frequently encounter sensations of pain, discomfort, challenges with communication, and eating, as well as noticeable changes in appearance and aesthetic deformity. These types of injuries also carry psychological implications and come with associated financial burdens.Aim: The aim of this research is to evaluate the epidemiology and fracture patterns associated with mandibular fractures in the region of Islamabad.Methodology: This prospective cross-sectional study was conducted in Islamabad, with a sample size of 170 patients determined using the WHO sample calculator. The sampling technique employed was non-probability consecutive sampling. A comprehensive case history was recorded by conducting both clinical and radiological examinations, including PA Face and OPG's (Orthopantomogram). The collected data were meticulously analyzed using SPSS version 23.0 for statistical analysis.Results: Among the 170 patients included in the study, the highest percentage of mandibular fractures occurred in individuals aged 18 to 30 years, with males accounting for 88.2% of the cases and females comprising only 11.2% of the population. Road traffic accidents were identified as the leading cause of mandibular fractures, representing 64.1% of the cases. The most common site of fracture was the para symphysis, observed in 16.5% of the patients. When examining combined fracture sites, the combination of the para symphysis and the angle of the mandible was the most frequent, accounting for 10% of cases.Conclusion: The leading cause of mandibular fractures and trauma was road traffic accidents (RTA). Mandibular fractures were more prevalent in men than women, with the majority of patients falling within the 18-30 age range. The parasymphysis emerged as the most common location for fractures, and in cases where fractures were concurrent, the parasymphysis and the mandibular angle exhibited the highest occurrence. There was a significant correlation between the type of injury mechanism and the precise anatomical site of the fracture. Understanding these associations is crucial for surgeons to determine the appropriate and timely management of mandibular fractures.